1999
DOI: 10.1088/0305-4470/32/19/309
|View full text |Cite
|
Sign up to set email alerts
|

Intertwining relations of non-stationary Schrödinger operators

Abstract: General first-and higher-order intertwining relations between non-stationary one-dimensional Schrödinger operators are introduced. For the first-order case it is shown that the intertwining relations imply some hidden symmetry which in turn results in a R-separation of variables. The Fokker-Planck and diffusion equation are briefly considered. Second-order intertwining operators are also discussed within a general approach. However, due to its complicated structure only particular solutions are given in some

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 24 publications
(67 reference statements)
3
68
0
Order By: Relevance
“…We have demonstrated that metric representations lead to consistent descriptions equivalent to the operator representation by providing further solutions to the time-dependent quasi-Hermiticity relation (4) and the time-dependent Dyson relation (5). For the spin models we considered here we observed that the determining relation for the metric operator (4) converts into as many equations as unknown functions.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…We have demonstrated that metric representations lead to consistent descriptions equivalent to the operator representation by providing further solutions to the time-dependent quasi-Hermiticity relation (4) and the time-dependent Dyson relation (5). For the spin models we considered here we observed that the determining relation for the metric operator (4) converts into as many equations as unknown functions.…”
Section: Discussionmentioning
confidence: 70%
“…Assuming the Dyson operator η(t) to be Hermitian, it can in principle be computed from ρ(t) by taking its square root. Subsequently one may compute the Hermitian counterpart h(t) by direct evaluation of the right-hand side of the time-dependent Dyson relation (5). As we will demonstrate in more detail below, taking the square root in this case can be rather awkward and to avoid this step we pursue here a different approach by solving the time-dependent Dyson relation first.…”
Section: H(t)φ(t) = I ∂ T φ(T) and Hψmentioning
confidence: 99%
See 2 more Smart Citations
“…For the one-dimensional case intertwining relations (30) were investigated in [19] for differential operators U(y, t) of first and second order in derivatives. While in the onedimensional problem a wide class of solutions was found, a straightforward extension to the two-dimensional case does not appear to be obvious.…”
Section: Time-dependent Exactly Solvable 3-body Matrix Problemsmentioning
confidence: 99%